BACTERIAL TRANSMISSION DYNAMICS IN ZOONOTIC AND HEALTHCARE-ASSOCIATED INFECTION CONTROL (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Bacterial pathogens operating across zoonotic and nosocomial transmission interfaces present compounding public health challenges that single-sector control frameworks consistently fail to address. This article integrates epidemiological evidence on bacterial zoonoses - including brucellosis, salmonellosis, leptospirosis, and tularemia - with data on healthcare-associated infections driven by antimicrobial-resistant organisms, examining shared transmission determinants and common pathogen ecology. The convergence of agricultural intensification, environmental contamination, and healthcare system vulnerabilities creates conditions in which pathogens establish multi-reservoir persistence. Evidence-based synthesis of One Health surveillance architectures, biosecurity interventions, and antimicrobial stewardship programs identifies coordinated control strategies that address both community-level zoonotic burden and institutional nosocomial risk simultaneously.